Determinations of iron speciation and modelling results of dissolved iron speciation and apparent iron solubility from water samples during METEOR cruise M136 - Kechen Zhu; Mark James Hopwood; Eric Pieter Achterberg; Martha Gledhill (PANGAEA, 2021)
The file contains measurements and modelling results of iron (Fe) speciation of water samples collected on the Peruvian shelf and slope region. Determinations of iron speciation were analyzed via Adsorptive Cathodic Stripping Voltammetry (Gledhill and Buck. 2012, Frontiers in Microbiology). Modelling results of dissolved iron speciation and the apparent Fe(III) solubility were calculated using the NICA-Donnan model (Kinniburgh et al. 1999, Colloids and Surfaces A) via chemical speciation software ORCHESTRA (Meeussen. 2003, Environ. Sci. Technol.).